TRAINING OF MAKING FEED SUPPLEMENT OF UMB HERBAL IN PARENGAN, TUBAN REGENCY - Siti Eliana Rochmi; Herinda Pertiwi; Agung Budianto Achmad; Retno Sri Wahjuni; Tri Wahyu Suprayogi; Tri Bhawono Dadi (Darmabakti Cendekia: Journal of Community Service and Engagements, 2020)
Background: Subdistrict Parengan has high livestock potential especially Suciharjo Village and Margorejo Village. The existing agricultural waste is not treated properly and livestock cannot reach maximum weights. The provision of quality animal feed is one of the efforts to improve the welfare of the community. Quality of animal feed can be increasing cattle productivity so that the selling value will increase. Purpose: This Community Service activity aims to improve the economic strengthening of the community through breeders through the introduction, dissemination, through technology UMB Herbal based on local resources that can increase the weight gain of beef cattle. UMB Herbal is a concentrate feed that uses raw materials based on raw materials (agriculture) with curcuma which is widely available in the regions. Improving skills makes UMB Herbal can be a provision for the community to be able to increase income. Methods: The method used in community service is the counseling for animal feed and health, training to make UMB Herbal and focus group discussions then applicating of UMB Herbal to pilot cattle. Results: The results of this community service include an increase in beef cattle body weight,  decreasing the gastrointestinal worm infestations, and increasing the knowledge and skills of the participants of the community service. Conclusion: Community Service Activities have a positive impact related to the development of beef cattle farms.